2019
DOI: 10.1074/jbc.ra118.006629
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E binds to and reduces serum levels of DNA-mimicking, pyrrolated proteins

Abstract: Lysine N-pyrrolation, converting lysine residues to Nϵ-pyrrole-l-lysine, is a recently discovered post-translational modification. This naturally occurring reaction confers electrochemical properties onto proteins that potentially produce an electrical mimic to DNA and result in specificity toward DNA-binding molecules such as anti-DNA autoantibodies. The discovery of this unique covalent protein modification provides a rationale for establishing the molecular mechanism and broad functional significance of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…The lysine N-pyrrolation, converting lysine residues to pyrK, is associated with an increased negative charge due to neutralization of the lysine residues and with conferring electrochemical properties onto proteins that potentially produce an electrical mimic to DNA (2). Our recent study has revealed that the apoE deficiency leads to significant accumulation of pyrrolated serum albumin and is associated with an enhanced immune response (3). This finding strongly suggested that a physiologically-relevant molecule might be involved in the lysine N-pyrrolation.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…The lysine N-pyrrolation, converting lysine residues to pyrK, is associated with an increased negative charge due to neutralization of the lysine residues and with conferring electrochemical properties onto proteins that potentially produce an electrical mimic to DNA (2). Our recent study has revealed that the apoE deficiency leads to significant accumulation of pyrrolated serum albumin and is associated with an enhanced immune response (3). This finding strongly suggested that a physiologically-relevant molecule might be involved in the lysine N-pyrrolation.…”
Section: Discussionmentioning
confidence: 93%
“…In our previous studies, we showed that the immunization of BALB/c mice with the pyrrolated proteins accelerated the production of autoantibodies (2). In addition, the age-dependent increase in the IgG and IgM titers to the dsDNA and pyrrolated proteins were observed in the SLE-prone MRL-lpr mice (2) and in the apoE-deficient mice (3). In the present study, to evaluate the biological significance of GA as a source of lysine N-pyrrolation, we examined the antigenic property of the GA-modified proteins and observed that the immunization with GA-modified BSA induced robust IgG production to the pyrrolated proteins ( Fig.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations